Knowledge and Practice of Rural Population Regarding Mosquito Control Measures: A Descriptive Study - Anu Joseph; Jhincy Jose; Aiswarya T. Jomon; Athira Ramesh; Chinnu Chandy; Gifta Sherina S.; Josely P.J.; Nimmy Sunny; Staicy Stanis; Stephy Thankachan (International Journal of Evidence Based Nursing And Practices, 2023)
The research aimed to evaluate the understanding and implementation of mosquito control strategies among the rural inhabitants in specific wards of the Athirampuzha panchayath. The study aimed to achieve the following objectives: evaluate the understanding of mosquito control measures among the rural population, analyze the implementation of mosquito control measures by the rural population, and investigate potential correlations between the rural population's knowledge of mosquito control measures and various demographic variables. A convenient sampling method was employed to select a sample of 30 individuals from the Athirampuzha panchayath rural population. Data was collected using a structured questionnaire to assess the rural population's knowledge and a checklist to evaluate their practices concerning mosquito control measures. The results showed that among 30 subjects, more than half of the samples 24 (80%) had average knowledge, 5 (16.7%) had poor knowledge and only 1 (3.3%) had good knowledge. In case of practice regarding mosquito control measures, majority of the samples, 25 (83.4%) had average practice, 4 (13.3%) had good practice and only 1 (3.3%) had poor practice. The study findings revealed that there is significant association between knowledge and gender and education of rural population regarding mosquito control measures and there is no significant association between knowledge score and other demographic variables. From this study it is indicated that majority of the subjects only have average knowledge regarding mosquito control measures.
Keywords: Athirampuzha panchayath; Knowledge; mosquito control measures; practice; rural population